Role of gut microbiota in predicting chemotherapy-induced neutropenia duration in leukemia patients - Huang, Yezi; Liao, Lihong; Jiang, Yanjun; Tao, Si; Tang, Duozhuang (Frontiers in Microbiology, 2025)
BackgroundAcute leukemia is an aggressive malignancy with high morbidity and mortality, and chemotherapy is the primary treatment modality. However, chemotherapy often induces neutropenia (chemotherapy-induced neutropenia, CIN), increasing the risk of infectious complications and mortality. Current research suggests that gut microbiota may play a significant role in chemotherapy’s efficacy and side effects.ObjectiveThis study aimed to investigate whether gut microbiota can predict the duration of chemotherapy-induced neutropenia in leukemia patients.MethodsWe included 56 leukemia patients from the Hematology Department of the Second Affiliated Hospital of Nanchang University, collecting fecal samples 1 day before and 1 day after chemotherapy. The diversity and community structure of gut microbiota were analyzed using 16S rRNA gene sequencing. Patients were divided into two groups based on the duration of neutropenia post-chemotherapy: Neutropenia ≤7 Days Group (NLE7 Group) and Neutropenia > 7 Days Group (NGT7 Group). Comparative analysis identified characteristic microbiota.ResultsAfter chemotherapy, gut microbiota diversity significantly decreased (p < 0.05). In the NGT7 Group, the relative abundance of Enterococcus before chemotherapy was significantly higher than in the NLE7 Group (p < 0.05). ROC curve analysis showed that the relative abundance of Enterococcus had high predictive accuracy for the duration of neutropenia (AUC = 0.800, 95% CI: 0.651–0.949).ConclusionThe abundance of Enterococcus before chemotherapy can predict the duration of chemotherapy-induced neutropenia. These findings provide new evidence for gut microbiota as a predictive biomarker for chemotherapy side effects and may guide personalized treatment for leukemia patients.